Quasi-physical phase compensation in digital holographic microscopy - Qu, Weijuan (2010)
In digital holographic microscopy, if an optical setup is well aligned, the phase curvature introduced by the microscope objective (MO) together with the illuminating wave to the object wave is a spherical phase curvature. It can be physically compensated by introducing the same spherical phase curvature in the reference beam. Digital holographic microscopy setups based on the Michelson interferometric configuration with MO and an adjustable lens are presented, which can well perform the quasi-physical phase compensation during the hologram recording. In the reflection mode, the adjustable lens serves as both the condensing lens and the compensation lens. When the spatial frequency spectra of the hologram become a point spectrum, one can see that the phase curvature introduced by imaging is quasi-physically compensated. A simple plane numerical reference wavefront used for the reconstruction can give the correct quantitative phase map of the test object. A theoretical analysis and experimental demonstration are given. The simplicity of the presented setup makes it easy to align it well at lower cost.